To find \((f \circ g)(x)\) and \((g \circ f)(x)\), we need to evaluate each function.
Given:
- \(f(x) = 7x^2\)
- \(g(x) = \frac{1}{x}\)
Part 1: Find \((f \circ g)(x)\)
The composition \((f \circ g)(x)\) means we will substitute \(g(x)\) into \(f(x)\):
-
Calculate \(g(x)\): \[ g(x) = \frac{1}{x} \]
-
Substitute \(g(x)\) into \(f(x)\): \[ (f \circ g)(x) = f(g(x)) = f\left(\frac{1}{x}\right) \]
-
Now plug \(\frac{1}{x}\) into \(f(x)\): \[ f\left(\frac{1}{x}\right) = 7\left(\frac{1}{x}\right)^2 \]
-
Simplify: \[ 7\left(\frac{1}{x}\right)^2 = 7 \cdot \frac{1}{x^2} = \frac{7}{x^2} \]
So, we have: \[ (f \circ g)(x) = \frac{7}{x^2} \]
Part 2: Find \((g \circ f)(x)\)
Now, we compute \((g \circ f)(x)\):
-
Substitute \(f(x)\) into \(g(x)\): \[ (g \circ f)(x) = g(f(x)) = g(7x^2) \]
-
Now plug \(7x^2\) into \(g(x)\): \[ g(7x^2) = \frac{1}{7x^2} \]
So, we have: \[ (g \circ f)(x) = \frac{1}{7x^2} \]
Final Answers
- \((f \circ g)(x) = \frac{7}{x^2}\)
- \((g \circ f)(x) = \frac{1}{7x^2}\)